CONTEMPORARY DANCE LIGHTING the poetry and the nitty-gritty. - Press, Carol M.; Scott, Vickie J. ([S.l.] : FOCAL, 2022)
Contemporary Dance Lighting: The Poetry and the Nitty-Gritty dynamically guides students toward aesthetically, creatively, and skillfully becoming lighting designers for dance in the 21st century. The book is organized in three parts, covering everything from the aesthetic considerations of lighting for dance to the tools and technology designers use to create compelling artistry. Part I, "Beginnings" establishes context, explaining the structure of the book and illuminating the history of contemporary dance and lighting. Part II, "The Poetry" elaborates on the key artistic and aesthetic elements of contemporary dance lighting: visual narrative; controllable functions and qualities of light; use of space, color, and time; importance and intricacies of collaboration; and continual effects and evolution of technology. Part III, "The Nitty-Gritty" steers students through the technical knowledge and skills necessary to design lighting, including understanding your tools and positioning instruments; creating layered light plots; organizing extensive paperwork; and archiving. The dance Artifice, choreographed by Jerry Pearson, is sequentially explored throughout the book to convey key concepts. "Further Reflections" conclude each chapter, written by a diverse group of renowned professionals, inviting young designers directly into the world of lighting design. This textbook is for use in Lighting Design and Design for Dance Lighting courses at the university level, along with professional training programs.
Keywords: PERFORMING ARTS / Theater / Stagecraft; PERFORMING ARTS / Dance / General; PERFORMING ARTS / Dance / Reference; Dance -- Stage-setting and scenery; Stage lighting; Dance -- Production and direction